Capital structure and its determinants in New Zealand firms - Wellalage, Nirosha Hewa; Locke, Stuart (Journal of Business Economics and Management, 2013)
The current study aims to empirically explore the relationship between firm characteristics, corporate governance and capital structure in New Zealand's large listed companies. Eight years of data for 40 firms listed on the NZX50 Stock Exchange, are collected and observations are analysed using a conditional quantile regression. This study finds firm-specific characteristics rather than corporate governance variables play a significant role in determining firm leverage levels. The results indicate that finance policies need to vary across firm type and firm characteristics, and should match with the different borrowing requirements of listed firms.